A modified conductive carbon black, carbon-coated slurry and carbon-coated aluminum foil and preparation method thereof
By performing ozonation modification treatment and polymerization reaction on conductive carbon black, the conductive polymer is grafted, and the problems of poor conductivity and easy solidification of the slurry are solved, thereby achieving carbon coating with high conductivity and good processing performance Slurry and ultra-low resistance carbon coated aluminum foil.
Patent Information
- Application Number
- CN202311691914.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-08
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-12-08
AI Technical Summary
The existing conductive carbon black has problems such as poor conductivity, excessive amount of binder, excessive moisture adsorption, and poor dispersion in lithium batteries, which affect the resistance and processing performance of the coating.
Epoxy groups are introduced through ozonation modification treatment and polymerized with conductive polymer monomers. The conductive polymer is grafted on the surface of conductive carbon black to enhance conductivity and fill pores, reducing moisture adsorption and binder usage.
It improves the conductivity and processing properties of conductive carbon black, reduces the coating resistance, avoids the problem of easy solidification of the slurry, and reduces the amount of adhesive used.
Smart Images

Figure BDA0004599468600000141 
Figure HDA0004599468760000011 
Figure HDA0004599468760000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium batteries, and in particular to a modified conductive carbon black, a carbon-coated slurry and a carbon-coated aluminum foil and a preparation method thereof. Background Art
[0002] In the field of lithium batteries, carbon-coated aluminum foil is used as a current collector for lithium batteries. A conductive network is formed by coating a carbon conductive agent on the surface of the aluminum foil to reduce the contact resistance between the aluminum foil and various positive electrode materials. The formation of a conductive network requires compounding conductive agents with different morphological characteristics, such as conductive carbon black and graphite. Graphite has a planar conjugated structure, and electrons can easily move along the π bond plane, but it is difficult for electrons to move between different graphite sheets, which hinders the flow of current. In order to achieve electronic conduction between graphite sheets, branched conductive nodes need to be added to connect the graphite sheets. Conductive nodes are usually served by conductive carbon black. The unique branched spherical structure of conductive carbon black can connect different graphite sheets to form a conductive network. Improving the conductivity of conductive carbon black and preparing a carbon-coated slurry with good processing performance are the keys to its excellent electrochemical properties. However, there are certain problems with conductive carbon black in practical applications, such as:
[0003] (1) Conductive carbon black has a branched spherical structure. Its branches and spherical structure bend the conjugated π bonds, resulting in poor electron mobility and conductivity. (2) The more branches conductive carbon black has, the greater its oil absorption value and porosity, and the greater its ability to connect to the conductive agent. However, when preparing the carbon coating slurry, the binder can easily enter the pores, resulting in an increase in the amount of binder and an increase in the resistance of the carbon coating layer. (3) The porosity of conductive carbon black is large, and it is easy to absorb too much water when preparing the carbon coating slurry. The slurry loses its free-flowing water and is prone to coagulation due to increased viscosity, which is not conducive to production and processing. (4) Conductive carbon black has a large specific surface area and poor dispersibility in the aqueous slurry system. It requires more binder to wet its surface to form a stable slurry. However, using too much binder will increase the resistance of the coating, which is not conducive to product performance.
[0004] At present, the methods to reduce coating resistance and improve slurry processing performance in the industry are mainly achieved by adjusting the formula and using equipment, such as using materials such as carbon nanotubes and graphene with better conductivity, or increasing the content of leveling additives, or using equipment with thinner coating thickness to improve the dispersion of conductive carbon black and reduce coating resistance. Among these methods, carbon nanotubes and graphene are too expensive, excessive additive content affects the electrochemical performance of the product, and it is difficult to improve the coating thickness of the coating equipment. The above methods all have different limitations.
[0005] Therefore, there is an urgent need to provide a method that can effectively improve the performance of conductive carbon black and carbon-coated slurry. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a modified conductive carbon black, a carbon-coated slurry and a carbon-coated aluminum foil and a preparation method thereof. The present invention can prepare a carbon-coated slurry with good processing performance and a carbon-coated aluminum foil with ultra-low resistance by using conductive carbon black modified by an intrinsic conductive polymer as a conductive agent.
[0007] To this end, the first aspect of the present invention provides a method for preparing a modified conductive carbon black, the preparation method comprising:
[0008] (1) conducting an ozonation modification treatment on the conductive carbon black to obtain an epoxy group-modified conductive carbon black;
[0009] (2) contacting the epoxy group-modified conductive carbon black with a conductive polymer monomer, wherein the conductive polymer monomer undergoes a polymerization reaction to obtain a conductive polymer which is grafted onto the surface of the conductive carbon black to obtain modified conductive carbon black.
[0010] Conductive carbon black is a branched spherical structure, and its branched chain and spherical structure bend the conjugated π bonds, resulting in poor electron mobility and conductivity. The present invention introduces epoxy groups into the surface of conductive carbon black through ozonation modification, and then introduces intrinsic conductive polymers into the surface of conductive carbon black through monomer polymerization and epoxy ring-opening reaction, thereby enhancing the conductivity of conductive carbon black and reducing resistance. At the same time, grafting intrinsic conductive polymers onto conductive carbon black with a branched spherical structure has the following advantages: (1) it can increase the conductive node structure, which is beneficial for subsequent compounding with graphite and increasing the electron conduction between graphite sheets; (2) the conductive polymer will partially fill the pores of the conductive carbon black, preventing excessive water from entering the pores. Using it in the preparation of carbon-coated slurry can improve the easy solidification phenomenon of the slurry due to loss of water fluidity, and at the same time can reduce the amount of binder and reduce resistance.
[0011] According to an embodiment of the present invention, the ozonation modification treatment in step (1) is carried out in an ozone atmosphere with an ozone partial pressure of 2-5 MPa.
[0012] According to an embodiment of the present invention, the ozonation modification treatment is carried out at 25-200°C, preferably 50-150°C.
[0013] According to an embodiment of the present invention, the time of the ozonation modification treatment is 0.5-24 hours, preferably 1-10 hours.
[0014] According to an embodiment of the present invention, step (1) further comprises, before the ozonation modification treatment, evacuating the reaction device for ozonation modification treatment so that the oxygen content in the reaction device is 10-100 ppm, preferably 10-50 ppm.
[0015] According to an embodiment of the present invention, the conductive polymerizable monomer in step (2) is selected from at least one of acetylene, pyrrole, aniline, carbazole, phenylacetylene, thiophene, thiadiazole, indole, benzothiazole, benzoxazole, oxadiazole, quinoxaline, thiadiazole, and pyridine. Thus, the intrinsic conductive polymer is introduced into the conductive carbon black through the polymerization reaction, thereby increasing the conductivity of the conductive carbon black.
[0016] According to an embodiment of the present invention, the raw materials for the polymerization reaction further include a first solvent and an initiator.
[0017] According to an embodiment of the present invention, the first solvent is selected from at least one of water, ethanol, methanol, acetone, tetrahydrofuran, acetonitrile, ethyl acetate, and N,N-dimethylformamide.
[0018] According to an embodiment of the present invention, the initiator is selected from at least one of benzoyl peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, hydrogen peroxide, ammonium persulfate, potassium persulfate, diisopropyl peroxydicarbonate, azobisisobutyronitrile, and tert-butyl perbenzoate.
[0019] According to an embodiment of the present invention, the mass ratio of the epoxy group-modified conductive carbon black to the conductive polymer monomer is 1:(0.05-0.3).
[0020] According to an embodiment of the present invention, the mass ratio of the initiator to the conductive polymer monomer is 1:(10-200).
[0021] According to an embodiment of the present invention, step (2) further includes: mixing the epoxy group-modified conductive carbon black, conductive polymer monomer, a first solvent, and an initiator to react, so that the conductive polymer monomer undergoes a polymerization reaction to obtain a conductive polymer and grafts it onto the surface of the conductive carbon black.
[0022] According to an embodiment of the present invention, the raw materials for the polymerization reaction further include an oxidant.
[0023] According to an embodiment of the present invention, step (2) also includes: mixing the epoxy group-modified conductive carbon black, conductive polymer monomer, a first solvent, an initiator, and an oxidant to react, so that the conductive polymer monomer undergoes a polymerization reaction to obtain a conductive polymer and grafts it onto the surface of the conductive carbon black.
[0024] According to an embodiment of the present invention, the oxidant is selected from at least one of ammonium persulfate, potassium dichromate, potassium iodate, hydrogen peroxide, potassium permanganate, and ferric chloride.
[0025] According to an embodiment of the present invention, the molar ratio of the conductive polymer monomer to the oxidant is 1:(1-2).
[0026] According to an embodiment of the present invention, the reaction temperature of the polymerization reaction is 50-200°C.
[0027] According to an embodiment of the present invention, the reaction time of the polymerization reaction is 0.5-10 hours.
[0028] According to an embodiment of the present invention, the reaction pressure of the polymerization reaction is 2-5 MPa.
[0029] The second aspect of the present invention provides a modified conductive carbon black, which is prepared by the preparation method described in the first aspect.
[0030] The modified conductive carbon black provided by the invention comprises an intrinsic conductive polymer in its structure, thereby increasing the conductivity and conductive nodes of the conductive carbon black.
[0031] A third aspect of the present invention provides a carbon coating slurry, the carbon coating slurry comprising: modified conductive carbon black, graphite and a dopant;
[0032] Wherein, the modified conductive carbon black is the modified conductive carbon black described in the second aspect;
[0033] The dopant is a transition metal halide.
[0034] The modified conductive carbon black structure provided by the present invention includes an intrinsic conductive polymer, which increases the conductivity and conductive nodes of the conductive carbon black. When used in combination with graphite, it can effectively increase the connection between different graphite sheets, which is conducive to the formation of a conductive network. The introduction of the intrinsic conductive polymer fills the pores of the conductive carbon black part. Due to the poor hydrophilicity of the conductive polymer, the excessive adsorption of water by the conductive carbon black is reduced, and the phenomenon of easy solidification of the slurry during pre-dispersion due to excessive loss of free-flowing water is avoided. At the same time, the introduction of the intrinsic electric copolymer conductive polymer also makes it possible to achieve the stability of the slurry wetting and dispersion during pre-dispersion by only wetting the outside of the conductive carbon black, reducing the amount of the binder, reducing the cost, and reducing the resistance. Therefore, the carbon-coated slurry provided by the present invention can take into account the conductivity and good processing performance of the conductive carbon black. In addition, the present invention uses transition metal halides as dopants, which can change the distribution of electron cloud orbits on the intrinsic conductive polymer polymer chain, increase the holes of the conductive polymer, reduce the energy barrier for electrons to move in large π bonds, further enhance the conductivity of the conductive nodes, facilitate electron transfer, and reduce resistance.
[0035] According to an embodiment of the present invention, the dopant includes at least one selected from niobium pentafluoride, tantalum pentafluoride, molybdenum pentafluoride, tungsten pentafluoride, ruthenium pentafluoride, platinum tetrachloride, and titanium tetrachloride. The dopants used in the present invention are all P-type dopants containing transition metal halides. The P-type dopant can change the distribution of electron cloud orbits on the intrinsic conductive polymer polymer chain, increase the holes of the conductive polymer, reduce the energy barrier for electrons to move in large π bonds, further enhance the conductivity of the conductive node, facilitate electron transfer, and reduce resistance.
[0036] According to an embodiment of the present invention, the carbon coating slurry further includes at least one of a binder, a dispersant, and a thickener.
[0037] According to an embodiment of the present invention, the binder is selected from at least one of acrylic resin, styrene-butadiene rubber resin, epoxy resin, and polyvinyl alcohol resin.
[0038] According to an embodiment of the present invention, the dispersant is selected from at least one of sodium dodecyl sulfate, BYK-ET3000, BYK-ET3001, BYK-ET3003, BYK-ET3004, BYK-ET3032, Electro-Rite AL003, BYK-ET3031, BYK-ET3002, BYK-ET3033, BYK-ET3034, and octadecyltrimethylammonium bromide.
[0039] According to an embodiment of the present invention, the thickener is selected from at least one of carboxymethyl cellulose, methyl cellulose, sodium carboxymethyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, polyethylene oxide, and polyvinyl pyrrolidone.
[0040] According to an embodiment of the present invention, the carbon coating slurry further includes a second solvent.
[0041] According to an embodiment of the present invention, the second solvent is selected from at least one of water, N-methylpyrrolidone and isopropanol.
[0042] According to an embodiment of the present invention, the mass ratio of the modified conductive carbon black to graphite is 1:(0.1-10).
[0043] According to an embodiment of the present invention, the mass ratio of the modified conductive carbon black to the dopant is 1:(0.01-0.2).
[0044] According to an embodiment of the present invention, the mass ratio of the total mass of the modified conductive carbon black and graphite to the binder is 1:(1-4).
[0045] According to an embodiment of the present invention, the mass ratio of the dispersant to the binder is 1:(20-100).
[0046] According to an embodiment of the present invention, the mass ratio of the thickener to the binder is 1:(10-100).
[0047] The fourth aspect of the present invention provides a method for preparing the carbon-coated slurry described in the third aspect, the preparation method comprising: mixing modified conductive carbon black, graphite, and a dopant to obtain the carbon-coated slurry.
[0048] According to an embodiment of the present invention, the preparation method further comprises mixing the modified conductive carbon black, graphite, a dopant with at least one of a binder, a dispersant, a thickener, and / or a second solvent to obtain the carbon coating slurry.
[0049] According to an embodiment of the present invention, the preparation method further comprises mixing modified conductive carbon black, graphite, a binder, a dopant, a dispersant, a thickener, and a second solvent, and performing stirring and sand milling to obtain the carbon-coated slurry.
[0050] According to an embodiment of the present invention, the stirring process is carried out at a speed of 500-1500 rpm.
[0051] According to an embodiment of the present invention, the temperature of the sanding treatment is 10-30°C.
[0052] According to an embodiment of the present invention, the sanding treatment time is 1-5 hours.
[0053] A fifth aspect of the present invention provides a method for preparing a carbon-coated aluminum foil, the method comprising coating a carbon-coated slurry on an aluminum foil substrate, and performing a drying process to obtain the carbon-coated aluminum foil;
[0054] Wherein, the carbon-coated slurry is the carbon-coated slurry described in the third aspect or is obtained by the preparation method described in the fourth aspect.
[0055] The preparation method of the carbon-coated aluminum foil provided by the present invention is based on a carbon-coated slurry including modified conductive carbon black, wherein the conductive carbon black is an intrinsic conductive polymer modified conductive carbon black, and the modified conductive carbon black can enhance the connection between conductive agents and facilitate the formation of a conductive network. The conductive carbon black is mixed with a binder, a transition metal halide dopant, an inorganic conductive agent, etc., and the processing performance of the carbon-coated slurry can be improved. The carbon-coated slurry is applied to the surface of the aluminum foil to form a conductive carbon layer with good leveling and ultra-low resistance.
[0056] According to an embodiment of the present invention, the temperature of the drying process is 80-200°C.
[0057] According to an embodiment of the present invention, the drying process takes 0.5-10 minutes.
[0058] According to an embodiment of the present invention, the coating thickness of the carbon coating slurry is 3-10 μm.
[0059] According to an embodiment of the present invention, the thickness of the aluminum foil substrate is 12-15 μm.
[0060] A sixth aspect of the present invention provides a carbon-coated aluminum foil, which is obtained by the preparation method described in the fifth aspect.
[0061] The beneficial effects of the present invention compared to the prior art are as follows:
[0062] (1) The present invention provides a method for modifying conductive carbon black with an intrinsic conductive polymer, wherein epoxy groups are introduced into the surface of the conductive carbon black through ozonation modification treatment, and then the intrinsic conductive polymer is introduced into the surface of the conductive carbon black through monomer polymerization reaction and epoxy ring-opening reaction, thereby enhancing the conductivity of the conductive carbon black and reducing the resistance;
[0063] (2) Grafting intrinsic conductive polymers onto conductive carbon black with a branched spherical structure can increase the conductive node structure, which is beneficial to increasing the electronic conduction between graphite sheets and facilitating the formation of a conductive network;
[0064] (3) Grafting the intrinsic conductive polymer onto the surface of the conductive carbon black, the conductive polymer will partially fill the pores of the conductive carbon black, preventing excessive water from entering the pores, and improving the easy solidification phenomenon of the carbon coating slurry due to the loss of water fluidity;
[0065] (4) The introduction of intrinsically conductive copolymerized polymer fills the internal pores of the conductive carbon black. During pre-dispersion, the binder only needs to wet the outside of the conductive carbon black to achieve the stability of the slurry wetting and dispersion, thereby reducing the amount of binder used, reducing costs, and lowering resistance.
[0066] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0068] Figure 1 A diagram showing the preparation process of conductive carbon black modified with epoxy groups in the preparation method of modified conductive carbon black provided by the present invention;
[0069] Figure 2 A process diagram showing a polymerization reaction in the method for preparing modified conductive carbon black provided by the present invention;
[0070] Figure 3 The composition diagram of the carbon coating slurry provided by the present invention is shown;
[0071] Figure 4 The morphology of the carbon-coated aluminum foil prepared in Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0072] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0073] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0074] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0075] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0076] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0077] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0078] According to an embodiment of the present invention, the present invention provides a modified conductive carbon black and a preparation method thereof. The modified conductive carbon black is based on conductive carbon black, which is a conductive agent with a branched spherical structure. Compared with a planar sheet structure, the spherical structure has moderate conductivity. Although the conductivity is not as good as that of flake graphite, due to its special branched spherical structure, it can form a conductive node, which is mainly used for connecting flake graphite in a conductive network. By ozonation modification treatment, epoxy groups are introduced into the surface of the conductive carbon black, and then by monomer polymerization reaction and epoxy ring-opening reaction, an intrinsic conductive polymer is introduced into the surface of the conductive carbon black, which can enhance the conductivity of the conductive carbon black and reduce the resistance.
[0079] The preparation method of the modified conductive carbon black comprises:
[0080] (1) Conductive carbon black is subjected to ozonation modification treatment to obtain conductive carbon black modified with epoxy groups.
[0081] The reaction process of this step can be seen in Figure 1, the conductive carbon black is subjected to ozonation modification treatment to obtain epoxy group-modified conductive carbon black.
[0082] According to a specific embodiment of the present invention, this step is carried out in an ozone atmosphere with an ozone partial pressure of 2-5 MPa. The ozonation modification treatment can be carried out at 25-200°C, preferably 50-150°C. The treatment time can be 0.5-24h, preferably 1-10h. In addition, before the ozonation modification treatment, the reaction device for the ozonation modification treatment needs to be vacuumed so that the oxygen content in the reaction device is 10-100ppm, preferably 10-50ppm. The reaction device includes but is not limited to a reactor.
[0083] According to a specific embodiment of the present invention, this step can be performed by the following method: add conductive carbon black to a high-pressure reactor, evacuate and replace with nitrogen several times to make the oxygen content in the reactor less than 100ppm, circulate the air in the reactor to suspend the conductive carbon black powder, start stirring, and heat to 25-200°C. Fill the reactor with ozone gas, keep the pressure in the reactor at high pressure, and make the partial pressure of ozone gas in the reactor between 2-5MPa. After reacting for 0.5-24 hours, evacuate and replace with nitrogen several times to obtain conductive carbon black modified with epoxy groups.
[0084] (2) contacting the epoxy group-modified conductive carbon black with a conductive polymer monomer, wherein the conductive polymer monomer undergoes a polymerization reaction to obtain a conductive polymer which is grafted onto the surface of the conductive carbon black to obtain modified conductive carbon black.
[0085] The reaction process of this step can be seen in Figure 2 , polymer-modified conductive carbon black is obtained through monomer polymerization reaction and epoxy ring-opening reaction.
[0086] According to a specific embodiment of the present invention, this step further includes: mixing the conductive carbon black modified by epoxy group and the conductive polymerization monomer, causing the conductive polymerization monomer to undergo polymerization reaction to obtain a conductive polymer and grafting it on the surface of the conductive carbon black. The conductive polymerization monomer includes but is not limited to acetylene, pyrrole, aniline, carbazole, phenylacetylene, thiophene, thiadiazole, indole, benzothiazole, benzoxazole, oxadiazole, quinoxaline, thiadiazole, pyridine, and other intrinsic conductive polymer monomers can also be used in the present invention. The raw materials of the polymerization reaction can also include a first solvent, an initiator, and an oxidant. The first solvent includes but is not limited to water, ethanol, methanol, acetone, tetrahydrofuran, acetonitrile, ethyl acetate, and N,N-dimethylformamide. The initiator includes but is not limited to benzoyl peroxide, tert-butyl peroxide benzoyl, methyl ethyl ketone peroxide, hydrogen peroxide, ammonium persulfate, potassium persulfate, diisopropyl peroxydicarbonate, azobisisobutyronitrile, and tert-butyl perbenzoate. The oxidant includes but is not limited to ammonium persulfate, potassium dichromate, potassium iodate, hydrogen peroxide, potassium permanganate, and ferric chloride. The mass ratio of the epoxy group-modified conductive carbon black to the conductive polymer monomer is 1:(0.05-0.3), the mass ratio of the initiator to the conductive polymer monomer is 1:(10-200), and the molar ratio of the conductive polymer monomer to the oxidant is 1:(1-2). The polymerization reaction is carried out at a temperature of 50-200°C for 0.5-10 hours, and the reaction pressure is 2-5MPa.
[0087] According to a specific embodiment of the present invention, this step can be performed by the following method: add conductive polymer monomers, deionized water, other solvents, initiators required for polymerization reaction through an auxiliary agent pump, and the oxidant can be reasonably selected according to the needs, start stirring, and heat to 50-200° C. Keep the pressure in the kettle at a high pressure of 2-5 MPa, react for 0.5-10 hours, filter the reaction liquid, ultrasonically clean it with water and ethanol for several times, filter it again, and vacuum dry it to obtain conductive carbon black modified with intrinsic conductive polymer.
[0088] According to an embodiment of the present invention, the present invention further provides a carbon coating slurry and a preparation method thereof, wherein the carbon coating slurry comprises modified conductive carbon black, graphite and a dopant;
[0089] Wherein, the modified conductive carbon black is the aforementioned modified conductive carbon black;
[0090] The dopant is a transition metal halide.
[0091] The carbon-coated slurry provided by the present invention includes the aforementioned modified conductive carbon black and is compounded with graphite to increase the conductive node structure, which is beneficial to increase the electronic conduction between graphite sheets, avoids sacrificing the conductivity of the conductive carbon black to improve the conductive properties of the graphite, and takes into account the conductivity of the conductive carbon black and the requirement of being a conductive node.
[0092] In addition, the looser the microstructure of conductive carbon black, the higher the porosity, the more node structures it has, and the more conducive it is to the formation of a conductive network. This is manifested in the higher the oil absorption value (DBP value), the better the conductivity. The structure of conductive carbon black is fluffy, and the volume of conductive carbon black is several times that of other carbon element conductive agents at the same mass. When making water-based carbon-coated slurry, it is hoped to use conductive carbon black with a large oil absorption value to increase the conductive nodes. However, due to the large oil absorption value of conductive carbon black, it is easy to absorb too much water into the pores during pre-dispersion, and the loss of free-flowing water makes the slurry easy to solidify, which is not conducive to processing and dispersion. Therefore, it is not easy to take into account both conductive properties and processing properties. The usual solution is to add more polymer binders. The binder not only has a film-forming effect, but also a wetting effect, which can promote the dispersion of the conductive agent in the solution. The binder will not only wet the surface of the conductive carbon black during pre-dispersion, but also enter the pores of the conductive carbon black. The larger the pores of the conductive carbon black of the same volume or mass, the more binder can be absorbed. However, too much binder will increase the coating resistance, which is not conducive to product application. Therefore, it is not easy to take into account both the process requirements such as wetting and dispersion and the low resistance requirements.
[0093] The carbon-coated slurry provided by the present invention is based on the aforementioned modified conductive carbon black. By grafting an intrinsic conductive polymer onto the surface of the conductive carbon black, the conductive polymer will partially fill the pores of the conductive carbon black, thereby preventing excessive water from entering the pores and reducing the entry of the binder, improving the easy solidification phenomenon of the slurry due to loss of water fluidity, reducing the amount of binder used, and reducing resistance.
[0094] According to a specific embodiment of the present invention, the dopant includes but is not limited to niobium pentafluoride, tantalum pentafluoride, molybdenum pentafluoride, tungsten pentafluoride, ruthenium pentafluoride, platinum tetrachloride, and titanium tetrachloride. In addition, the carbon-coated slurry may also include a binder, a dispersant, a thickener, and a second solvent. The binder includes but is not limited to acrylic resin, styrene-butadiene rubber resin, epoxy resin, and polyvinyl alcohol resin. The dispersant includes but is not limited to sodium dodecyl sulfate, BYK-ET3000, BYK-ET3001, BYK-ET3003, BYK-ET3004, BYK-ET3032, Electro-Rite AL003, BYK-ET3031, BYK-ET3002, BYK-ET3033, BYK-ET3034, and octadecyl trimethyl ammonium bromide. The thickener includes but is not limited to carboxymethyl cellulose, methyl cellulose, sodium carboxymethyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, polyethylene oxide, and polyvinyl pyrrolidone. The second solvent includes but is not limited to water, N-methylpyrrolidone, and isopropanol. The mass ratio of modified conductive carbon black, graphite, and dopant is 1:(0.1-10):(0.01-0.2). The mass ratio of the total mass of modified conductive carbon black and graphite to the binder is 1:(1-4). The mass ratio of dispersant to binder is 1:(20-100). The mass ratio of thickener to binder is 1:(10-100). The present invention can change the electron cloud orbital distribution on the intrinsic conductive polymer polymer chain, increase the holes of the conductive polymer, reduce the energy barrier for electron movement in large π bonds, and further enhance the conductivity of the conductive node by adding a P-type transition metal halide dopant to the carbon-coated slurry.
[0095] According to an embodiment of the present invention, the method for preparing the carbon-coated slurry includes mixing modified conductive carbon black, graphite, and a dopant to obtain the carbon-coated slurry.
[0096] According to an embodiment of the present invention, the preparation method further comprises mixing the modified conductive carbon black, graphite, a dopant with at least one of a binder, a dispersant, a thickener, and / or a second solvent to obtain the carbon coating slurry.
[0097] According to a specific embodiment of the present invention, the preparation method may further include mixing the modified conductive carbon black, graphite, binder, dopant, dispersant, thickener and second solvent, stirring and sand milling to obtain the carbon coating slurry. The stirring speed may be 500-1500 rpm, and the sand milling temperature may be 10-30°C for 1-5h.
[0098] According to a specific embodiment of the present invention, the preparation method of the carbon-coated slurry can be specifically as follows: water, a binder, intrinsic conductive polymer modified conductive carbon black, graphite, a dopant, a dispersant and a thickener are mixed, and then pre-dispersed uniformly by mechanical stirring at a high speed, and the stirring speed is 500-1500 rpm. The pre-dispersed slurry is sand-milled at 10-30°C for 1-5 hours to obtain a carbon-coated slurry. The composition of the slurry can be found in Figure 3 .
[0099] According to an embodiment of the present invention, the present invention also provides a carbon-coated aluminum foil and a preparation method thereof, the preparation method comprising coating a carbon-coated slurry on an aluminum foil substrate and performing a drying treatment to obtain the carbon-coated aluminum foil, wherein the carbon-coated slurry is the aforementioned carbon-coated slurry or is obtained by the aforementioned preparation method.
[0100] When making carbon-coated aluminum foil, it is necessary to apply a conductive agent on the surface to form a conductive network as a channel for electron transmission. Conductive carbon black and graphite are used as the conductive agents of the mainstream slurry. Conductive carbon black has a spherical structure and weak conductivity. Graphite is a large conjugated sheet structure with strong conductivity. Electrons can be conducted along the planar π bonds, but it is not easy to conduct between graphite sheets, which hinders the flow of current. Conductive nodes need to be added for conduction between graphite sheets. Conductive nodes connect different sheets of graphite together, so they need to have a very small particle size and branched claw morphology. Conductive nodes are usually served by conductive carbon black with a branched spherical structure. Therefore, in order to form a conductive network, conductive agents with different morphological characteristics must be added. Conductive agents are generally compounded from two components, namely "conductive carbon black for conductive nodes" and "graphite with good conductivity." The conductive agent in the carbon-coated aluminum foil provided by the present invention includes intrinsic conductive polymer modified conductive carbon black, which not only enhances the conductivity and increases the conductive node structure, which is beneficial to increase the electronic conduction between graphite sheets, but also improves the processing performance of the carbon-coated slurry, reduces the use of binders, and prepares carbon-coated slurry with good processing performance and ultra-low resistance carbon-coated aluminum foil.
[0101] According to a specific embodiment of the present invention, in the preparation method of the carbon-coated aluminum foil, the drying process can be performed at 80-200° C. for 0.5-10 min. The coating thickness of the carbon-coated slurry can be 3-10 μm, and the thickness of the aluminum foil substrate is 12-15 μm, but it is not limited to the above numerical range, and those skilled in the art can make reasonable adjustments according to actual preparation requirements.
[0102] The reaction process of this step can be specifically as follows: the slurry can be coated by a wire rod, a scraper or a micro-concave roller. The carbon-coated slurry is coated on the surface of the aluminum foil substrate with a thickness of 12-15 μm by a coating machine, and the coating wet film thickness is controlled to be 3-10 μm. The aluminum foil with the coating is placed in a drying machine and heated at 80-200°C for 0.5-10 minutes to form a film. After drying, it is compacted by a roller press to obtain the carbon-coated aluminum foil.
[0103] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0104] Example 1
[0105] The method provided by the present invention is used to prepare carbon-coated aluminum foil, comprising the following steps:
[0106] (1) Evacuate the sealed autoclave and replace it with nitrogen several times. After replacement, the oxygen content in the autoclave is less than 30ppm. Add 100 parts of conductive carbon black to the autoclave, circulate the air in the autoclave to suspend the conductive carbon black powder, and start stirring. Fill the reaction kettle with ozone gas, maintain the ozone partial pressure in the autoclave to 4MPa, raise the temperature to 80°C, react for 2 hours, turn off the air circulation in the autoclave after the reaction is completed, evacuate and replace it with nitrogen several times to obtain epoxy group-modified conductive carbon black;
[0107] (2) Add 500 parts of deionized water, 10 parts of pyrrole, 37 parts of ammonium persulfate and 0.5 parts of tert-butyl perbenzoate into a sealed autoclave, stir mechanically until uniform, heat to 80°C, maintain the pressure in the autoclave at 4MPa, and react for 2 hours. After the reaction is completed, filter, and ultrasonically clean the solid with water and ethanol three times, and then vacuum dry at 75°C to obtain intrinsic polypyrrole modified conductive carbon black;
[0108] (3) 100 parts of deionized water, 20 parts of K-702 binder, 5 parts of intrinsic polypyrrole modified conductive carbon black, 5 parts of graphite KS-6, 0.5 parts of BYK-ET3003, 0.5 parts of tantalum pentafluoride and 1 part of carboxymethyl cellulose were weighed by mass, and the mixture was stirred at a high speed of 1000 rpm until uniform. The pre-dispersed carbon slurry was sand-milled at 10° C. for 2 hours to obtain a carbon-coated slurry;
[0109] (4) The carbon-coated slurry was coated on a plain aluminum foil using a 5 μm wire rod, and then dried at 150°C for 5 minutes to form a film. After drying, the carbon-coated aluminum foil was compacted by roller pressing. The morphology of the carbon-coated aluminum foil is shown in FIG. Figure 4 .
[0110] Example 2
[0111] The method provided by the present invention is used to prepare carbon-coated aluminum foil, comprising the following steps:
[0112] (1) Evacuate the sealed autoclave and replace it with nitrogen several times. After replacement, the oxygen content in the autoclave is less than 30ppm. Add 100 parts of conductive carbon black to the autoclave, circulate the air in the autoclave to suspend the conductive carbon black powder, and start stirring. Fill the reactor with ozone gas, maintain the ozone partial pressure in the autoclave to 5MPa, raise the temperature to 90°C, and react for 3 hours. After the reaction is completed, turn off the air circulation in the autoclave, evacuate and replace it with nitrogen several times to obtain epoxy group-modified conductive carbon black;
[0113] (2) Add 10 parts of acetylene and 0.5 parts of tert-butyl perbenzoate to a sealed autoclave, circulate air in the autoclave to suspend the conductive carbon black powder, start stirring, maintain the pressure in the autoclave at 5 MPa, raise the temperature to 180°C, and react for 2 hours. After the reaction is completed, filter, and ultrasonically clean the solid with water and ethanol three times, and then vacuum dry at 75°C to obtain intrinsic polyacetylene modified conductive carbon black;
[0114] (3) Weigh 100 parts of deionized water, 20 parts of K-702 binder, 5 parts of intrinsic polyacetylene modified conductive carbon black, 5 parts of graphite KS-6, 0.5 parts of BYK-ET3001, 0.5 parts of titanium tetrachloride and 1 part of carboxymethyl cellulose by mass, stir them at a high speed until they are uniform, and the stirring speed is 1000 rpm. Sand grind the pre-dispersed carbon slurry with a sand mill at 10° C. for 2 hours to obtain a carbon-coated slurry;
[0115] (4) The carbon-coated slurry is coated on a plain aluminum foil using a 5 μm wire rod, and then baked at 150° C. for 5 minutes to form a film. After drying, the film is compacted by roller to obtain the carbon-coated aluminum foil.
[0116] Example 3
[0117] The method provided by the present invention is used to prepare carbon-coated aluminum foil, comprising the following steps:
[0118] (1) Evacuate the sealed autoclave and replace it with nitrogen several times. After replacement, the oxygen content in the autoclave is less than 30ppm. Add 100 parts of conductive carbon black to the autoclave, circulate the air in the autoclave to suspend the conductive carbon black powder, and start stirring. Fill the reaction kettle with ozone gas, maintain the ozone partial pressure in the autoclave to 4MPa, raise the temperature to 80°C, react for 2 hours, turn off the air circulation in the autoclave after the reaction is completed, evacuate and replace it with nitrogen several times to obtain epoxy group-modified conductive carbon black;
[0119] (2) Add 200 parts of deionized water, 300 parts of ethanol, 15 parts of thiophene, 32 parts of ferric chloride and 0.5 parts of tert-butyl perbenzoate into a sealed autoclave, stir mechanically until uniform, heat to 80°C, maintain the pressure in the autoclave at 4MPa, and react for 2 hours. After the reaction is completed, filter, and ultrasonically clean the solid with water and ethanol three times, filter and vacuum dry at 75°C to obtain intrinsic polythiophene modified conductive carbon black;
[0120] (3) 100 parts of deionized water, 20 parts of K-702 binder, 5 parts of intrinsic polythiophene modified conductive carbon black, 5 parts of graphite KS-6, 0.5 parts of BYK-ET3003, 0.5 parts of tantalum pentafluoride and 1 part of carboxymethyl cellulose were weighed by mass, and the mixture was stirred at a high speed of 1000 rpm until uniform. The pre-dispersed carbon slurry was sand-milled at 10° C. for 2 hours to obtain a carbon-coated slurry;
[0121] (4) The carbon-coated slurry is coated on a plain aluminum foil using a 5 μm wire rod, and then baked at 150° C. for 5 minutes to form a film. After drying, the film is compacted by roller to obtain the carbon-coated aluminum foil.
[0122] Example 4
[0123] The method provided by the present invention is used to prepare carbon-coated aluminum foil, comprising the following steps:
[0124] (1) Evacuate the sealed autoclave and replace it with nitrogen several times. After replacement, the oxygen content in the autoclave is less than 30ppm. Add 100 parts of conductive carbon black to the autoclave, circulate the air in the autoclave to suspend the conductive carbon black powder, and start stirring. Fill the reaction kettle with ozone gas, maintain the ozone partial pressure in the autoclave to 4MPa, raise the temperature to 80°C, react for 2 hours, turn off the air circulation in the autoclave after the reaction is completed, evacuate and replace it with nitrogen several times to obtain epoxy group-modified conductive carbon black;
[0125] (2) Add 200 parts of ionized water, 300 parts of ethanol, 10 parts of phenylacetylene and 0.5 parts of diisopropyl peroxydicarbonate into a sealed autoclave, stir mechanically until uniform, heat to 80°C, maintain the pressure in the autoclave at 4Mpa, and react for 2 hours. After the reaction is completed, filter, and ultrasonically clean the solid with water and ethanol three times, filter, and vacuum dry at 75°C to obtain intrinsic polyphenylacetylene modified conductive carbon black;
[0126] (3) Weigh 100 parts of deionized water, 20 parts of K-702 binder, 5 parts of intrinsic polyphenylene vinylene modified conductive carbon black, 5 parts of graphite KS-6, 0.5 parts of BYK-ET3003, 0.5 parts of ruthenium pentafluoride and 1 part of carboxymethyl cellulose by mass, stir them at a high speed until they are uniform, and the stirring speed is 1000 rpm. Sand grind the pre-dispersed carbon slurry with a sand mill at 10° C. for 2 hours to obtain a carbon-coated slurry;
[0127] (4) The carbon-coated slurry is coated on a plain aluminum foil using a 5 μm wire rod, and then baked at 150° C. for 5 minutes to form a film. After drying, the film is compacted by roller to obtain the carbon-coated aluminum foil.
[0128] Comparative Example 1
[0129] (1) 100 parts of deionized water, 20 parts of K-702 binder, 5 parts of conductive carbon black (commercially available unmodified conductive carbon black), 5 parts of graphite KS-6, 0.5 parts of BYK-ET3003, 0.5 parts of tantalum pentafluoride and 1 part of carboxymethyl cellulose were weighed by mass, and the mixture was stirred at a high speed of 1000 rpm until uniform. The pre-dispersed carbon slurry was sand-milled at 10° C. for 2 hours to obtain a carbon-coated slurry;
[0130] (2) The carbon-coated slurry is coated on a plain aluminum foil using a 5 μm wire rod, and then baked at 150° C. for 5 minutes to form a film. After drying, the film is compacted by roller to obtain the carbon-coated aluminum foil.
[0131] Comparative Example 2
[0132] (1) Weigh 100 parts of deionized water, 20 parts of K-702 binder, 5 parts of intrinsic polypyrrole-modified conductive carbon black prepared in Example 1, 5 parts of graphite KS-6, 0.5 parts of BYK-ET3003 and 1 part of carboxymethyl cellulose by mass, stir them at a high speed until they are uniform, and the stirring speed is 1000 rpm. Sand grind the pre-dispersed carbon slurry with a sand mill at 10° C. for 2 hours to obtain a carbon-coated slurry;
[0133] (2) The carbon-coated slurry is coated on a plain aluminum foil using a 5 μm wire rod, and then baked at 150° C. for 5 minutes to form a film. After drying, the film is compacted by roller to obtain the carbon-coated aluminum foil.
[0134] Comparative Example 3
[0135] (1) 100 parts of deionized water, 50 parts of K-702 binder, 5 parts of intrinsic polypyrrole modified conductive carbon black prepared in Example 1, 5 parts of graphite KS-6, 0.5 parts of BYK-ET3003, 0.5 parts of tantalum pentafluoride and 1 part of carboxymethyl cellulose were weighed by mass, and the mixture was stirred at a high speed of 1000 rpm until uniform. The pre-dispersed carbon slurry was sand-milled at 10° C. for 2 hours to obtain a carbon-coated slurry;
[0136] (2) The carbon-coated slurry is coated on a plain aluminum foil using a 5 μm wire rod, and then baked at 150° C. for 5 minutes to form a film. After drying, the film is compacted by roller to obtain the carbon-coated aluminum foil.
[0137] Performance Testing:
[0138] The carbon-coated aluminum foils obtained in Examples 1-4 and Comparative Examples 1-3 were tested and analyzed for their performance, including:
[0139] (1) Oil absorption value (DBP) test: Brabender carbon black oil absorption meter type C, test the volume number (cm2) of dibutyl phthalate (DBP) absorbed by 100g carbon black 3 ), which is used to characterize the aggregation degree of carbon black.
[0140] (2) Specific surface area (BET) test: Bester nitrogen adsorption specific surface area tester.
[0141] (3) Viscosity test: rotational viscometer.
[0142] (4) Particle size test: laser particle size analyzer.
[0143] (5) Pre-dispersion properties and coating leveling: visual inspection.
[0144] (6) Thickness test: thickness gauge.
[0145] (7) Resistance, resistivity and conductivity test: two-probe resistance tester.
[0146] (8) Peel strength test: INSTRON tensile testing machine.
[0147] The results are shown in Tables 1-3.
[0148] Table 1 Conductive carbon black performance test results
[0149] Example 1 Example 2 Example 3 Example 4 Unmodified conductive carbon black <![CDATA[Oil absorption value (cm 3 / 100 g)]]> 182 174 185 191 156 <![CDATA[Specific surface area (m 2 / g)]]> 125 134 119 112 147
[0150] Table 2 Carbon coating slurry performance test results
[0151] Viscosity (mPa·s) <![CDATA[Particle size D 50 (μm)]]> Pre-dispersed properties Coating leveling Example 1 55.3 0.3209 Good liquidity Uniform Example 2 52.9 0.3126 Good liquidity Uniform Example 3 55.6 0.3195 Good liquidity Uniform Example 4 51.8 0.3265 Good liquidity Uniform Comparative Example 1 450.4 0.2845 Viscous, gel-like Horizontal stripes Comparative Example 2 60.8 0.3185 Good liquidity Uniform Comparative Example 3 80.5 0.3128 Good liquidity Uniform
[0152] Table 3 Carbon coated aluminum foil performance test results
[0153]
[0154] Among them, it can be seen from Table 1 and Table 3 that:
[0155] (1) The oil absorption value of the intrinsic conductive polymer modified conductive carbon black prepared in Examples 1-4 is greater than that of the unmodified conductive carbon black, indicating that the branched structure increases after modification, and the conductive nodes increase accordingly, which is conducive to the connection and formation of the conductive network. At the same time, compared with the unmodified conductive carbon black, the conductivity of the carbon-coated aluminum foil prepared with the intrinsic conductive polymer modified conductive carbon black is also greater;
[0156] (2) The specific surface area of the intrinsic conductive polymer modified conductive carbon black prepared in Examples 1-4 is smaller than that of the unmodified conductive carbon black, indicating that the surface area of the same mass of carbon black is reduced, and the amount of binder required to wet the carbon black surface is reduced. Reducing the amount of binder is beneficial to reducing the coating resistance.
[0157] From Table 2 and Table 3, we can see that:
[0158] (1) Comparative Example 1 Compared with Example 1, the intrinsic conductive polymer modified conductive carbon black in Example 1 is replaced with commercially available unmodified conductive carbon black, and the viscosity of the corresponding carbon coating slurry increases, and the pre-dispersed slurry is viscous, resulting in uneven coating and low coating adhesion. At the same time, since Comparative Example 1 uses commercially available unmodified conductive carbon black, its conductive nodes are not increased, and the conductivity of the carbon-coated aluminum foil obtained in Comparative Example 1 is less than that in Example 1;
[0159] (2) Comparative Example 2 Compared with Example 1, no dopant was added in Comparative Example 2, resulting in poor conductivity of the obtained carbon-coated aluminum foil;
[0160] (3) Compared with Example 1, Comparative Example 3 increases the amount of binder used. Due to the poor conductivity of the binder, the resistance of the conductive carbon layer increases.
[0161] In summary, combined with the test results, it can be seen that by grafting intrinsic conductive polymers onto conductive carbon black, the conductivity of conductive carbon black can be improved, the conductive nodes can be increased, and it can be used to prepare carbon-coated slurry. The easy solidification phenomenon of the slurry due to the loss of water fluidity can be improved, while the amount of binder can be reduced, the resistance is reduced, and a carbon-coated slurry with good processing performance and an ultra-low resistance carbon-coated aluminum foil can be prepared.
[0162] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0163] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing modified conductive carbon black, characterized in that: The preparation method comprises: (1) Conductive carbon black is subjected to ozonation modification treatment to obtain conductive carbon black modified with epoxy groups; (2) contacting the epoxy group-modified conductive carbon black with a conductive polymer monomer, wherein the conductive polymer monomer undergoes a polymerization reaction to obtain a conductive polymer which is grafted onto the surface of the conductive carbon black to obtain a modified conductive carbon black; Wherein, the ozonation modification treatment in step (1) is carried out in an ozone atmosphere with an ozone partial pressure of 2-5 MPa; The ozonation modification treatment is carried out at 25-200°C; The time of the ozonation modification treatment is 0.5-24h; Step (1) further comprises, before the ozonation modification treatment, evacuating the reaction device for ozonation modification treatment so that the oxygen content in the reaction device is 10-100 ppm; The conductive polymerizable monomer in step (2) is at least one selected from acetylene, pyrrole, aniline, carbazole, phenylacetylene, thiophene, thiadiazole, indole, benzothiazole, benzoxazole, oxadiazole, quinoxaline, thiadiazole, and pyridine; The raw materials for the polymerization reaction also include a first solvent and an initiator; The first solvent is selected from water, ethanol, methanol, acetone, tetrahydrofuran, acetonitrile, ethyl acetate, N,N - At least one of dimethylformamide; The initiator is selected from at least one of benzoyl peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, hydrogen peroxide, ammonium persulfate, potassium persulfate, diisopropyl peroxydicarbonate, azobisisobutyronitrile, and tert-butyl perbenzoate; The mass ratio of the epoxy group-modified conductive carbon black to the conductive polymer monomer is 1:(0.05-0.3); The mass ratio of the initiator to the conductive polymer monomer is 1:(10-200); The reaction temperature of the polymerization reaction is 50-200°C; The reaction time of the polymerization reaction is 0.5-10 hours.
2. The preparation method according to claim 1, characterized in that: The ozonation modification treatment is carried out at 50-150°C.
3. The preparation method according to claim 1, characterized in that: The time of the ozonation modification treatment is 1-10 hours.
4. The preparation method according to claim 1, characterized in that: The vacuum treatment makes the oxygen content in the reaction device 10-50 ppm.
5. A modified conductive carbon black, characterized in that: The modified conductive carbon black is prepared by the preparation method according to any one of claims 1 to 4.
6. A carbon coating slurry, characterized in that: The carbon coating slurry comprises: modified conductive carbon black, graphite and dopant; Wherein, the modified conductive carbon black is the modified conductive carbon black according to claim 5; The dopant includes at least one selected from niobium pentafluoride, tantalum pentafluoride, molybdenum pentafluoride, tungsten pentafluoride, ruthenium pentafluoride, platinum tetrachloride, and titanium tetrachloride; The carbon coating slurry also includes a binder, a dispersant, a thickener, and a second solvent; The binder is selected from at least one of acrylic resin, styrene-butadiene rubber resin, epoxy resin and polyvinyl alcohol resin; The dispersant is at least one selected from sodium lauryl sulfate, BYK-ET3000, BYK-ET3001, BYK-ET3003, BYK-ET3004, BYK-ET3032, Electro-Rite AL003, BYK-ET3031, BYK-ET3002, BYK-ET3033, BYK-ET3034, and octadecyltrimethylammonium bromide; The thickener is selected from at least one of carboxymethyl cellulose, methyl cellulose, sodium carboxymethyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, polyethylene oxide, and polyvinyl pyrrolidone; The second solvent is selected from water, N- At least one of methyl pyrrolidone and isopropyl alcohol; The mass ratio of the modified conductive carbon black to graphite is 1:(0.1-10); The mass ratio of the modified conductive carbon black to the dopant is 1:(0.01-0.2); The mass ratio of the total mass of the modified conductive carbon black and graphite to the mass ratio of the binder is 1:(1-4); The mass ratio of the dispersant to the binder is 1:(20-100); The mass ratio of the thickener to the binder is 1:(10-100).
7. A method for preparing the carbon coating slurry according to claim 6, characterized in that: The preparation method comprises mixing modified conductive carbon black, graphite, a dopant with a binder, a dispersant, a thickener and a second solvent to obtain the carbon coating slurry.
8. A method for preparing a carbon-coated aluminum foil, characterized in that: The preparation method comprises coating a carbon-coated slurry on an aluminum foil substrate and performing a drying process to obtain the carbon-coated aluminum foil; Wherein, the carbon-coated slurry is the carbon-coated slurry according to claim 6 or is obtained by the preparation method according to claim 7.
9. The preparation method according to claim 8, characterized in that: The temperature of the drying process is 80-200°C.
10. The preparation method according to claim 8, characterized in that: The drying time is 0.5-10 min.
11. A carbon-coated aluminum foil, characterized in that: The carbon-coated aluminum foil is obtained by the preparation method according to any one of claims 8 to 10.
Citation Information
Patent Citations
Anode water-based carbon-coated aluminum foil coating and preparation method thereof
CN115241424A
Preparation of highly conductive organic polymer film
JP1992068032A
Conducting polymer-grafted carbon material for fuel cell applications
US20040166401A1